VipIMAGE 2017 Proceedings of the VI ECCOMAS Thematic Conference on Computational Vision and Medical Image Processing Porto, Portugal, October 18-20, 2017 (Lecture Notes in Computational Vision and Biomechanics,, 2018)
This book gathers papers presented at the VipIMAGE 2017-VI ECCOMAS Thematic Conference on Computational Vision and Medical Image Processing. It highlights invited lecturers and full papers presented at the conference, which was held in Porto, Portugal, on October 18-20, 2017. These international contributions provide comprehensive coverage on the state-of-the-art in the following fields: 3D Vision, Computational Bio-Imaging and Visualization, Computational Vision, Computer Aided Diagnosis, Surgery, Therapy and Treatment, Data Interpolation, Registration, Acquisition and Compression, Industrial Inspection, Image Enhancement, Image Processing and Analysis, Image Segmentation, Medical Imaging, Medical Rehabilitation, Physics of Medical Imaging, Shape Reconstruction, Signal Processing, Simulation and Modelling, Software Development for Image Processing and Analysis, Telemedicine Systems and their Applications, Tracking and Analysis of Movement, and Deformation and Virtual Reality. In addition, it explores a broad range of related techniques, methods and applications, including: trainable filters, bilateral filtering, statistical, geometrical and physical modelling, fuzzy morphology, region growing, grabcut, variational methods, snakes, the level set method, finite element method, wavelet transform, multi-objective optimization, scale invariant feature transform, Laws' texture-energy measures, expectation maximization, the Markov random fields bootstrap, feature extraction and classification, support vector machines, random forests, decision trees, deep learning, and stereo vision. Given its breadth of coverage, the book offers a valuable resource for academics, researchers and professionals in Biomechanics, Biomedical Engineering, Computational Vision (image processing and analysis), Computer Sciences, Computational Mechanics, Signal Processing, Medicine and Rehabilitation.